2020
DOI: 10.1007/s41403-020-00129-3
|View full text |Cite
|
Sign up to set email alerts
|

Optimising Lockdown Policies for Epidemic Control using Reinforcement Learning

Abstract: There has been intense debate about lockdown policies in the context of Covid-19 for limiting damage both to health and to the economy. We present an AI-driven approach for generating optimal lockdown policies that control the spread of the disease while balancing both health and economic costs. Furthermore, the proposed reinforcement learning approach automatically learns those policies, as a function of disease and population parameters. The approach accounts for imperfect lockdowns, can be used to explore a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
31
0
7

Year Published

2020
2020
2022
2022

Publication Types

Select...
4
4
1

Relationship

1
8

Authors

Journals

citations
Cited by 48 publications
(38 citation statements)
references
References 5 publications
0
31
0
7
Order By: Relevance
“…Essential services, supply chains, and some parts of the market must remain active since households cannot retain supplies and remain self-sufficient for such extended periods. Therefore, a practical PWQ can at most be implemented at a level of η = 70-75% 49 .…”
Section: Resultsmentioning
confidence: 99%
“…Essential services, supply chains, and some parts of the market must remain active since households cannot retain supplies and remain self-sufficient for such extended periods. Therefore, a practical PWQ can at most be implemented at a level of η = 70-75% 49 .…”
Section: Resultsmentioning
confidence: 99%
“…Permasalahan yang kemudian terjadi setelah diterapkannya physical distancing dan social distancing adalah merubah proses pembelajaran di sekolah menjadi belajar di rumah ini kemudian memberikan dampak yang signifikan terhadap perkembangan Pendidikan siswa. Pembelajaran yang selalu di kelas dengan berbagai metode pembelajaran baik konvensional maupun inovasi metode menjadi terhambat (Khadilkar et al, 2020;Mussardo, 2019;Uscher-Pines et al, 2018). salah satu jenjang Pendidikan yang paling dipengaruhi oleh penerapan lockdown adalah jenjang Pendidikan Anak Usia Dini (PAUD).…”
Section: Pendahuluanunclassified
“…Biasanya pembelajaran diberikan sepenuhnya kepada guru di sekolah dalam mendidik anak. Akan tetapi sekarang setelah adanya wabah covid-19 kemudian mengharuskan orang tua sebagai guru dan juga sekolah bagi anak (Khadilkar et al, 2020). Proses aktivitas anak pada masa lockdown bervariasi, hal ini dikarenakan setiap anak memiliki aktivitasnya sendiri Ketika di rumah.…”
Section: Pendahuluanunclassified
“…They demonstrated that DQL can be useful in the context of epidemiological decision-making. Khadilkar et al [21] proposed a methodology to compute optimal lockdown/release policies learnt with a RL algorithm in the context of COVID-19 pandemic. They considered the function of disease parameters (infectiousness, gestation period, duration of symptoms, and probability of death) and population characteristics (density, movement propensity).…”
Section: Artificial Intelligence To Fight Covid-19mentioning
confidence: 99%